고성능 공핍모드 n형 유기전기화학트랜지스터 - 신동준 (The Graduate School, Ajou University, 2024)
Organic electrochemical transistors (OECTs) have gained tremendous attention due to their low-voltage operation, high amplification, and ion-to-electron coupling. These advancements are particularly notable in the development of biocompatible and flexible sensors, as well as e-skin multifunctional circuits. Despite these advancements, the practical application of OECTs, where n-type and p-type materials complement each other, is challenging. This is largely due to the performance disparity between p-type and n-type organic mixed ionic-electronic conductors (OMIECs) used in OECT channels, with n-type OMIECs facing issues, such as low electron mobility, slow operation speed, and instability. To address these challenges, this study focuses on exploring the operational characteristics of n-type OECTs using newly synthesized X-material. The research demonstrates that OECTs utilizing X-material exhibit impressive performance metrics, including high charge carrier mobility, rapid transient response, and enhanced long-term stability. All results indicate that X-material can effectively complement p-type counterparts. Furthermore, the study introduces an innovative concept in the form of an anti-ambipolar electrochemical transistor. This transistor operates through ion injection-driven resistance modulation, presenting a novel approach to transistor design. Overall, this research significantly contributes to enhancing the performance of next-generation organic electronic devices, potentially revolutionizing the field.
학위논문(석사)--지능형반도체공학과,2024. 2
Keywords: Heterojunction structure; Organic electrochemical transistors; Organic mixed ionic-electronic conductor; Side-chain free polymer